Water Quality Index of southern part of the Kathmandu Valley, Central Nepal; evaluation of physical water quality parameters of shallow wells - Bohara, Bimal (Bulletin of the Department of Geology, 2016)
Physical water quality of shallow groundwater of the southern part of the Kathmandu Valley was studied and analysed. Being the capital city of the country, the population is increasing day by dayand consequently the demand of water supply has also increased. Analyses reveal ranges of temperature to be 15.3–24.2 °C, pH to be 5.67–8.07, electrical conductivity to be (EC) 230–2860 μS/cm, and dissolved oxygen (DO) to be 0.09–9.1 mg/L in dry season whereas in wet season temperature, pH, EC and DO ranges are respectively 19.6–27.3 °C, 5.92–8.3, 183–3030 μS/cm and 0.19–7.9 mg/L. Water Quality Index (WQI) map shows that the upstream river areas contain good water quality than the downstream areas. The areas like Kalanki and Satdobato have poor water quality according to the guidelines of Nepal Drinking Water Quality Standard.Bulletin of the Department of Geology, Vol. 19, 2016, pp. 45–56